Analisis Kebutuhan dan Pengembangan Kompetensi Pengawas Sekolah Dasar di Kabupaten Pidie - Jafriany, Yuni; Musdiani, Musdiani; Novita, Rita (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to analyze the needs of elementary school supervisors in Pidie District and to develop strategies to enhance their competence.Method – The research method utilizes a qualitative descriptive approach through interviews, observations, and documentary studies. The results indicate deficits in supervision and insufficient competence. Recommendations include increasing the number of supervisors and providing further training. This study is expected to enhance the quality of elementary education supervision in Pidie.Findings – The research findings indicate a deficit in the number of supervisors and insufficient competence in Kabupaten Pidie. The proposed recommendations include increasing the number of supervisors and implementing advanced training programs. Through these efforts, it is hoped that this study can significantly contribute to enhancing the quality of supervision in basic education in Pidie, thereby improving overall teaching and school management processes. Research Implications – The research improves supervision quality by pinpointing ineffective areas needing enhancement. Tailoring resources to specific needs optimizes supervisor numbers and task distribution for better outcomes. Findings also inform enhanced education policies for elementary school management and supervision. However, challenges unique to Kabupaten Pidie require a nuanced, contextual approach beyond general analyses.